The Effects of Acidified Sodium Chlorite and Acidified Sodium Chlorite Containing Sauce on Listeria monocytogenes in Chicken Chops - Yalçın, Halil; Aydın, Isıl; Arslan, Ali (My University, 2018)
This study was aimed to investigate the effects of acidified sodium chlorite (ASC) and ASC containing sauce on chicken chops contaminated with ;Listeria monocytogenes. ;Chickenchops were experimentally contaminated with ;L. monocytogenes.For the bacterial inhibition, the chops were treated with sauce, ASC (200 ppm and 1800 ppm) and ASC containing sauce. ;The groups are planned according to the proportions of decontaminants applied and the estimated shelf life of the product.Contaminated 8 groups chops (1 group contaminated control)were placed in plastic containers, and kept at 4 ;°C for 7 days. The samples were investigated in terms of ;L. monocytogenesat 0., 2., 3., 5. and 7. days. It was determined that there was statistically significant difference between groups in terms of number of ;L. monocytogenes. The highest decrease in number of ;L. monocytogeneswas determined in group 6 on day 7 as 1.85 log10cfu/g. In this study, the highest antimicrobial effect on ;L. monocytogeneswas found in chicken chops kept after holding it for 2 minutes in solution containing 1800 ppm ASC. In conclusion, ASC solution decreases the risk of ;L. monocytogenesin chicken chops.
Keywords: Listeria monocytogenes; Decontamination; Acidified Sodium Chlorite; Chicken Chop; Sauce